Être mère d’un·e adolescent·e suivi·e pour un cancer : un travail de care genré et socialement différencié - Zoé Rollin (Association Anthropologie Médicale Appliquée au Développement et à la Santé, 2021)
Based on two periods of socio-ethnographic fieldwork conducted with teenagers and young adults and their parents, this article seeks to investigate how the context of the onset of a serious health event such as cancer modifies a mother’s work. Situated in an interactionist approach, this article studies the "social management of the disease" (Strauss, 1992) from a sociological and collective point of view by focusing on the scholastic side of disease management as a heuristic observation point to grasp certain dimensions of a mother’s work. The main purpose of this article is to highlight the work of mothers of adolescents, whose daily lives are particularly affected by the onset of serious illness.